2014
DOI: 10.7717/peerj.257
|View full text |Cite
|
Sign up to set email alerts
|

Absence ofHelicobacter pyloriis not protective against peptic ulcer bleeding in elderly on offending agents: lessons from an exceptionally low prevalence population

Abstract: Aim. Helicobacter pylori (H. pylori) infection is exceptionally rare in population from the north-eastern region of Peninsular Malaysia. This provides us an opportunity to contemplate the future without H. pylori in acute non-variceal upper gastrointestinal (GI) bleeding.Methods. All cases in the GI registry with GI bleeding between 2003 and 2006 were reviewed. Cases with confirmed non-variceal aetiology were analysed. Rockall score > 5 was considered high risk for bleeding and primary outcomes studied were in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Interestingly, none of the eight patients diagnosed with peptic ulcers were positive for H. pylori in our study. A recent report in an elderly population found that the absence of H. pylori infection did not reduce the risk of bleeding peptic ulcers in patients with other risk factors, especially those who were receiving drug treatments [35]. Unfortunately, we did not obtain information on the usage of non-steroidal anti-inflammatory drugs that are also an important factor for the development of peptic ulcers [36].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, none of the eight patients diagnosed with peptic ulcers were positive for H. pylori in our study. A recent report in an elderly population found that the absence of H. pylori infection did not reduce the risk of bleeding peptic ulcers in patients with other risk factors, especially those who were receiving drug treatments [35]. Unfortunately, we did not obtain information on the usage of non-steroidal anti-inflammatory drugs that are also an important factor for the development of peptic ulcers [36].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, after antibiotic usage against H. pylori and, of course, its eradication in Western countries, a constant equilibrium between H. pylori and human health disappeared. Interestingly, in Northeastern Malaysia, the low prevalence of H. pylori infection was frequently reported ( 36 38 ). As general rule, one expects that frequency of diseases such as asthma and GERD should be relatively low rather than the findings of expected inverse association were not found ( 39 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, eradication of H. pylori is insufficient to avoid NSAID-associated ulcers as proton pump inhibitors, according to a meta-analysis [15]. Despite the fact that proton pump inhibitors (PPIs), H2 blockers, and prostaglandin E1 analogs give some protection against stomach ulcers [16], the adverse effect rate of these drugs could prohibit them from being used in clinical practice [17]. Experiments in several animal models have demonstrated that herbal medications can effectively prevent the formation of gastric ulcers while having fewer adverse effects, suggesting that herbal medicines could be used to prevent gastric and/or duodenal ulcers [3].…”
Section: Introductionmentioning
confidence: 99%